Effect of Different Modifications (Physical and Chemical) on Morphological, Pasting, and Rheological Properties of Black Rice (Oryza sativa L. Indica) Starch: A Comparative Study. (27th September 2020) - Dhull, Sanju Bala; Punia, Sneh; Kumar, Manoj; Singh, Shivdeep; Singh, Parhlad
Abstract: The demand for black rice has increased rapidly in the past years because of the distinctive color, characteristic flavor, nutritional value, and health benefits. This study aims to investigate the chemical and physical modifications on morphology, pasting, thermal, and rheological properties of black rice starch. The highest swelling power is observed for octenyl succinic anhydride modified black rice starch whereas gamma irradiated rice starch shows the lowest value. Rheometer analysis shows that physical and chemical modifications generally alter the pasting characteristics of starches which may be attributed to the excessive degradation of starch granules. Native black rice starch granules are of small size and irregular in shapes with sharp angles and edges. After modifications, rice starch granules surface lose natural morphology. All native and modified rice starch exhibit the typical A‐type X‐ray patterns of cereal starches. Results of present study provides a better understanding of functional properties of native and modified black rice starches for their possible applications in food products. Abstract : Black rice starch is a naturally occurring glucose homo‐polysaccharide of nutritional, pharmaceutical, and industrial importance. The structure and functionality of the native black rice starch is modified by physical (thermal and non‐thermal) and chemical methods. These modification techniques have led to some revolutionary changes in functionality, and application of black rice starch in the nutritional, pharmaceutical, biomedical, and industrial field.